A study of Neonatal Sepsis and to assess the validity of sepsis screen as a diagnostic tool - Dr. Sunny Juneja; Dr. Prachi Chaudhary; Dr. S Thora; Dr. Sunil Arya (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Neonatal sepsis is the leading cause of neonatal mortality in the developing world. There is an increasing incidence of drug resistance among organisms. We have tried to the sepsis profile in our nursery and to assess the validity of sepsis screen as a diagnostic tool. We have also studied the individual parameters of the screen for their strength as a diagnostic tool. Methods: This was a prospective study carried out in the SCNU of MY Hospital and included 200 newborns with suspected sepsis. Sepsis Screen and Blood Cultures were done in all the babies and the results were analysed. Results: Out of the 200 patients with suspected sepsis, 150 (75%) had a positive sepsis screen whereas 102 (51%) were culture positive. Sepsis Screen was positive in 93.1% of total culture positive sepsis and in 56.1% of culture negative cases too. Thus, the Sensitivity and specificity for Septic Screen was calculated to be 93.18 and 43.88% repetitively. PPV was 63.33% and NPV was 86.0 %. Conclusion: The bacteriological flora has changed over the last 12 years and there has been a high incidence of resistance to the first live antibiotics in our Nursery. The sepsis screen has a high negative predictive value and it is recommended that negative sepsis screen should warrant discontinuation of the empirical antibiotics to prevent the unnecessary use and the emergence of drug resistant organisms.